THE ROLE OF ZONAL COUNCIL AND THE NORTH EASTERN COUNCIL IN INDIA’S FEDERAL STRUCTURE - Singh, Narendra Bahadur; Ankit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India’s federal system has evolved significantly, with various institutional mechanisms designed to foster cooperative federalism and address regional disparities. Two such critical entities are the Zonal Councils and the North Eastern Council, which play pivotal roles in promoting cultural unity, resolving regional challenges, and advancing socio-economic development across the country. Zonal Councils, established to facilitate dialogue between states, serve as platforms for addressing issues like resource allocation, linguistic tensions, and inter-state coordination. Their primary goal is to cultivate a collaborative spirit and resolve regional problems, thereby contributing to the overall advancement of India’s federal structure. These councils’ function across five geographical zones, each with its own unique demographic and economic profiles. Additionally, the North Eastern Council, created in 1971, specifically focusses on the socio-economic development of India’s northeastern states, recognizing their strategic importance and ethnic diversity. These states face unique challenges, such as border disputes, linguistic conflicts, and developmental disparities, which the North Eastern Council aims to address through cooperative planning. Both the Zonal Councils and the North Eastern Council play a crucial role in reducing tensions between the center and the states, fostering a collaborative spirit, and promoting balanced regional development. The article underscores the significance of the Zonal Councils, the division of Zones, the composition and functions of these councils, the North Eastern Council, and their role in nurturing a federal character to enhance their efficiency. By grouping states based on their shared demographic and economic characteristics, these councils can enhance coordination and maximize the potential for regional development, ultimately strengthening India’s federal framework and promoting balanced growth across the country.